Rejecting a religiousness of the Enlightenment. The dismantling of the measures promoted by Pablo de Olavide in the New Settlements of Sierra Morena and Andalusia - Pérez-Schmid Fernández, Francisco José; Hamer Flores, Adolfo (Cuadernos de Historia Moderna, 2021)
The purpose of this article is to analyze how, after imprisonment and condemnation of Pablo de Olavide, the model of religiosity that he had tried to establish in the New Settlements of Sierra Morena and Andalusia underwent a rapid transformation that led him to resemble any other location of the surroundings in a few years. This process had not only the impulse of the civil and, above all, ecclesiastical authorities but also the willingness and collaboration of the residents of these new colonies that, in many cases, did not share or understand the religiosity that Olavide tried to promote among them.